Endangered Andean cat distribution beyond the Andes in Patagonia - Novaro, Andres Jose (2010)
The endangered Andean cat Leopardus jacobita was considered an endemic of the Andes at altitudes above 3,000 m, until it was discovered in the Andean foothills of central Argentina in 2004. We carried out surveys for Andean cats and sympatric small cats in the central Andean foothills and the adjacent Patagonian steppe, and found Andean cats outside the Andes at elevations as low as 650 m. We determined that Andean cats are widespread but rare in the northern Patagonian steppe, with a patchy distribution. Our findings suggest that the species’ distribution may follow that of its principal prey, the rock-dwelling mountain vizcacha.